КУЛЬТУРНЫЕ ИННОВАЦИИ В БИБЛИОТЕКЕ ИМ. «М.В. ЛОМОНОСОВА» - ЩЕЛЧКОВА, директор библиотеки-филиала им. М. В. Ломоносова, Маргарита (BIBLIOPOLIS, 2020)
The article focuses on the cultural and educational innovation of the branch, which allow readers to use the new, non-standard services that contribute to the production of public recognition and acquisition of social significance, so necessary to libraries at the present stage.